Pengembangan Media Pembelajaran Audio Visual Berbasis Film Pendek pada Materi Hikayat Siswa Kelas X SMA Bina Taruna Medan - Devi, Gabriella Gayatri; Rita, Rita; Soraya, Ratna (Medan Resource Center, 2024)
This study aimed to develop and assess the feasibility of short film-based audio-visual learning media for class X SMA, focusing on saga material. Using the modified Borg and Gall development model with eight steps, including research, planning, product draft development, individual and small group trials, revisions, and improvements. Results showed that the short film-based media received high validity and feasibility ratings from two media experts (94% and 92%) and two material experts (91.3% and 72%). The Indonesian language teacher assessed it as 86%